The influence of preparation conditions on the electro-acoustic properties of the PZT-type piezoceramic sensors - J. DUDEK; L. KOZIELSKI; Z. SUROWIAK; M. F. KUPRIYANOV (Archives of Acoustics)
The possibilities of the application of the microstructure analysis, X-ray powder diffraction, and Raman scattering methods for the fast and reliable control of the quality of piezoelectric ceramic sensors at every stage of preparation are shown.